Self-Reports of Sexual Violence Outside of Survey Reference Periods: Implications for Measurement - Dufour, Gena K. (Journal of interpersonal violence, 2023)
Accurate measurement of sexual violence (SV) victimization is important for informing research, policy, and service provision. Measures such as the Sexual Experiences Survey (SES) that use behaviorally specific language and a specified reference period (e.g., since age 14, over the past 12 months) are considered best practice and have substantially improved SV estimates given that so few incidents are reported to police. However, to date, we know little about whether estimates are affected by respondents’ reporting of incidents that occurred outside of the specified reference period (i.e., reference period errors). The current study explored the extent, nature, and impact on incidence estimates of reference period errors in two large, diverse samples of post-secondary students. Secondary analysis was conducted of data gathered using a follow-up date question after the Sexual Experiences Survey–Short Form Victimization. Between 8% and 68% of rape and attempted rape victims made reference period errors, with the highest proportion of errors occurring in the survey with the shortest reference period (1 month). These errors caused minor to moderate changes in time period-specific incidence estimates (i.e., excluding respondents with errors reduced estimates by up to 7%). Although including a date question does not guarantee that all time period-related errors will be identified, it can improve the accuracy of SV estimates, which is crucial for informing policy and prevention. Researchers measuring SV within specific reference periods should consider collecting dates of reported incidents as best practice.